Perceptions of Teachers, Guardians and Students on The Use of The Zoom Application As A Learning Platform in Elementary Schools : Persepsi Guru, Wali Murid dan Siswa Terhadap Pemanfaatan Aplikasi Zoom Sebagai Platform Pembelajaran di Sekolah Dasar - Frida Hidayati Subarto; Feri Tirtoni (Academia Open, 2022)
Online or online learning is considered a solution for teaching and learning activities to continue in the midst of the corona pandemic. This happened due to the increasing number of the spread of the corona virus in Indonesia which prompted the government to issue several policies intended to avoid the spread of the corona virus to students in various schools. Online learning can use one application as a learning platform, one of which is the Zoom Meeting application, which is carried out in learning in elementary schools (SD). The purpose of this study was to determine the perceptions of teachers, parents and students on the use of the application. However, their perception requires support from all elements of education, be it the central government, local government and the community to jointly build a conducive environment for students to learn wherever they are, as well as become a stimulus in efforts to overcome learning difficulties from within. them, especially in the midst of the current pandemic. The study was conducted at 3 public elementary schools in Surabaya using 440 samples from the elements of teachers, parents and students, with observations, interviews and questionnaires as data collection methods. Based on the analysis of the collected data, it can be concluded that the perceptions of teachers, parents and students are positive towards the use of the Zoom Meeting application as a learning platform in Elementary Schools (SD), with 86% on the knowledge indicator, 62% on the attitude indicator and 72% on the assessment indicator.